2007
DOI: 10.1038/sj.cgt.7701099
|View full text |Cite
|
Sign up to set email alerts
|

E1A-expressing adenoviral E3B mutants act synergistically with chemotherapeutics in immunocompetent tumor models

Abstract: The majority of clinical trials evaluating replication-selective oncolytic adenoviruses utilized mutants with immunomodulatory E3B genes deleted, likely contributing to the attenuated efficacy. We investigated whether an intact immune response could contribute to the observed improved efficacy in response to combinations with chemotherapeutics. Seven carcinoma cell lines were evaluated by combining viral mutants; dl309 (DE3B), dl704 (DE3gp19K), dl312 (DE1A) or wild-type Ad5 with the commonly used clinical drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…Complete elimination of tumors was not possible with either Ad5-3D-A20T or Ad5wt because of limitations of the in vivo model. Murine tissues do not support productive infection with human adenovirus, preventing spread within the murine tumor microenvironment in addition to the rapid xenograft growth and the absence of an immune response (49). Despite the rapid hepatic elimination of adenovirus in mice, we confirmed that intravenous delivery of Ad5-3D-A20T resulted in high levels of viral gene expression in Suit-2 tumors.…”
Section: Discussionsupporting
confidence: 61%
“…Complete elimination of tumors was not possible with either Ad5-3D-A20T or Ad5wt because of limitations of the in vivo model. Murine tissues do not support productive infection with human adenovirus, preventing spread within the murine tumor microenvironment in addition to the rapid xenograft growth and the absence of an immune response (49). Despite the rapid hepatic elimination of adenovirus in mice, we confirmed that intravenous delivery of Ad5-3D-A20T resulted in high levels of viral gene expression in Suit-2 tumors.…”
Section: Discussionsupporting
confidence: 61%
“…46,47 We speculate that early viral E1A expression was responsible for most of the synergistic effects based on the fact that E1A is a potent apoptosis inducer and synergizes with apoptosis-inducing cytotoxic drugs. [34][35][36]48 Adenoviral E1A proteins can interact with numerous cellular effector molecules such as tumor necrosis factora, NO, TNF-related apoptosis-inducing ligand, Fas ligand (reviewed in ref. 49 ) and immune cells, including NK cells, macrophages and T cells, promoting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Potent E1A expression was a requirement even in cells not supporting viral replication, in agreement with earlier reports. [34][35][36] Importantly, we demonstrate that E1A with the pRb-binding region deleted in dl922-947 can synergistically interact with 5-FU and gemcitabine in pancreatic cancer cells. Both replicationdependent and -independent mechanisms were indicated in the synergistic responses.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations